Kepemimpinan Transformasional, Motivasi Kerja Guru Dan Kompetensi Guru Terhadap Kinerja Guru Serta Implikasinya Pada Kompetensi Lulusan - Masduki Heryana (Kontigensi : Jurnal Ilmiah Manajemen, 2015)
The purpose of this study was to analyze the effect of transformational leadership, motivation of teachers and teacher competence on teacher performance and the implications on the competence of senior high school graduates international in West Java Province. The research method using descriptive survey and explanatory survey methods. The unit of analysis in this study is consists of permanent and non-permanent teachers who teaches at the school of international standard in 25 regencies / cities in West Java Province that consists of 38 national high schools and four private high school. Path Analysis Method was used to test the hypothesis. The results can be summarized as follows: 1). Transformational leadership significantly influence the performance of teachers. 2). Motivational leadership is not significant effect on teachers performance3). Competence of teachers significantly influence the performance of teachers. 4). Transformational leadership, motivation and competence of teachers simultaneously affect the performance of teachers. 5). Teacher performance indirectly affect the performance of graduates.